Attachment to land and its downfalls: Can policy encourage land mobility?. (January 2023) - Bradfield, Tracy; Butler, Robert; Dillon, Emma J.; Hennessy, Thia; Loughrey, Jason
Abstract: Sentimental ties to land in Ireland result in less than 1 percent of agricultural land being sold each year and land rental is among the lowest of countries in the European Union. The findings highlight that longer leases are associated with large farms and those with a high percentage of land rented in, but revised policies are required to encourage more landowners to rent out their land. Improved land mobility can reduce issues such as barriers to entry for farmers, the economic vulnerability of farms, low farm succession rates, low pensions and an ageing farmer population. The history of land in Ireland and the non-pecuniary benefits of farming are also discussed. Highlights: The history of agricultural land in Ireland has resulted in strong sentimental and cultural ties to land. Low land mobility in Ireland is evidenced by the fact that less than 1 percent of agricultural land is sold each year and Ireland has one of the lowest land rental rates in the European Union. The findings highlight that longer leases are associated with large farms and those with a high percentage of land rented in. Policies to increase long-term lease agreements have been somewhat successful. However, there is little possibility of most farms being able to maximise the tax relief that is available.